Encyclopedia of water science - Trimble, Stanley Wayne (CRC Press, 2008)
Issues addressed included: Climate; Irrigation; Land use and water; Regional and historical case studies; Research; Soil and plant water; Streams and channels; Water characteristics, chemistry, pollution, and pollution control; and Water law.